The institutionalization of a regional order by circulation: establishing and self-establishing as a Southern African freshwater bureaucracy - (:unkn) unknown (My University, 2022)
Since the 1990s, a regional freshwater bureaucracy has been institutionalized in southern Africa. Through circulation within its boundaries, a group of agents has established a bureaucracy equipped with formal institutions. In return, circulation amongst its elites has given this group the opportunity to establish itself as a key part of this bureaucracy. The structuring effect of this circulation has in term injected uncertainly into the regional order: caught between contradictory injunctions, it is not formally sedimented, meaning that it is institutionalizing more than it is institutionalized. It is precisely through the investment of agents similar social properties, the establishment of allegiances and institutional frames that a regional bureaucracy unfold. By analysing the processes and their effects, the case study tackles circulation and uncertainty (of this institutionalization process) as modes of government.
Keywords: African Research